3D-printed monolithic SiCN ceramic microreactors from a photocurable preceramic resin for the high temperature ammonia cracking process. Issue 8 (27th June 2019) - Gyak, Ki-Won; Vishwakarma, Niraj K.; Hwang, Yoon-Ho; Kim, Jeehwan; Yun, Hui-suk; Kim, Dong-Pyo
Abstract : A SiCN ceramic microreactor with high temperature tolerance and chemical resistance has been fabricated by a 3D printing method. Abstract : This research describes a 3D-printed SiC-based ceramic microreactor for ammonia cracking, for hydrogen production, at high temperature, which reveals its robust sustainability for highly corrosive chemical processes. This research reports the fabrication of fully dense 3D-printed SiCN ceramic monoliths with various shapes and structures via pyrolysis at 1000°C of the green bodies derived from a photocurable preceramic composite resin containing 10 wt% of silica nanoparticle filler as a ceramic precursor. Upon the pyrolytic conversion to the ceramic dense structures, the polymeric features on a scale of several centimeters retained their shapes with no deformation and no cracks owing to uniform isotropic shrinkage and relatively low weight loss. With the well-defined ceramic microreactor, ammonia cracking for hydrogen production was conducted from 600 to 1000°C at different flow rates and showed high conversion rates up to 99%. The ceramic microreactor showed excellent heat tolerance and chemical resistance. The combination of preceramic resin and additive manufacturing technology provides breakthrough approaches for complex-shaped and extremely resistant non-oxide ceramic systems.